Study Interaction the Impact of Problem Based Learning and Thinking Learning Models Creative to Performance Studying Social Sciences - Sofiana, Nina; Misnah, Misnah; Herlina, Herlina (Journal of Education Method and Learning Strategy, 2024)
Learning model Problem based learning (PBL) is a student - centered learning model , where student Study solve problem in accordance material learning in a way independent . Whereas ability think creative student is ability student in create your own ideas . Understand interaction between the PBL model and capabilities think creative can give valuable insight​ For increase performance Study student . Research purposes This namely : (1) examine interaction the impact of the PBL model on performance students ' social studies learning , (2) studying interaction impact think creative to performance study , (3) study interaction impact of PBL models and thinking creative to performance Study . Research design This use design phenomenology , in activity Data analysis follows stages of the Miles and Huber analysis process . And technique analysis of the data used is technique analysis descriptive . Research result This shows : (1) Yes interaction the positive impact of the PBL learning model on performance students learn social studies . (2) Yes interaction positive impact​ ability think creative student to performance Study . (3) Yes interaction positive impact of the PBL learning model and abilities think creative student to performance study social studies. (4) Yes interaction more impact​ large PBL learning model towards performance Study than ability think creative student.